Investigating anxiety in oral recitation among freshmen BS accountancy students in a Philippine higher education institution - Bactol, Clint Joseph; Acabado, Airene; Canales, Alyssa; Taborada, Angelica; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
In higher education curriculum, oral recitation is one of the frequent methods utilized in assessing the learnings accumulated by the students throughout the entire topic. Adam (2017) stated that oral recitation is a direct, teacher-centered approach in which the instructor asks succinct questions with a predetermined response in mind. Subsequently, it is unavoidable for students to become anxious when they are being asked to recite in front of the class. In this regard, students should identify their coping strategies and techniques on how they will effectively manage their anxiety of oral recitation. The study was conducted in qualitative approach utilizing Interpretative Phenomenological Analysis. A total of 26 participants who are first year college students were selected through the Purposive-convenience sampling method. Using thematic analysis, the findings indicated four reasons behind students' anxiety of oral recitation, namely; unpleasant past experiences, self-evaluation, fear of rejection, and lack of preparation and training. Also, based on thematic analysis, five underlying factors that are encountered by the students based on their provided reasons were emerged. The factors were: anxious of making mistakes, perfectionism, classroom set-up and environment, linguistic insecurity in English language, and cramming and procrastination. The participants in this research endeavor likewise disclosed their preparations before an oral recitation such as advance reading and crafting possible questions, reminding for having a sure oral recitation, and fulfilling physiological needs for a better performance. Coping techniques during oral recitation to ease their anxiety were also revealed by the participants such as exercising the importance of proper breathing and body gestures and avoiding intrusive thoughts.